Fully coupled atmospheric‐hydrological modeling at regional and long‐term scales: Development, application, and analysis of WRF‐HMS. Issue 4 (29th April 2016) - Wagner, Sven; Fersch, Benjamin; Yuan, Fei; Yu, Zhongbo; Kunstmann, Harald
Abstract: A closed description of the regional water balance requires hydro‐meteorological modeling systems which represent the atmosphere, land surface, and subsurface. We developed such a mesoscale modeling system, extending the atmospheric model WRF with the distributed hydrological model HMS in a fully coupled way. It includes explicit lateral groundwater and land surface flow parameterization schemes and two‐way groundwater‐unsaturated zone interaction by replacing the free drainage bottom boundary of WRF's Noah‐LSM with a Fixed‐head or Darcy‐flux boundary condition. The system is exemplarily applied for the Poyang Lake basin (160, 000 km 2 ) and the period 1979–1986 using a two‐nest approach covering East Asia (30 km) and the Poyang Lake basin (10 km) driven by ERA Interim. Stand‐alone WRF effectively simulates temperature (bias 0.5°C) and precipitation (bias 21–26%). Stand‐alone HMS simulations provide reasonable streamflow estimates. A significant impact on the regional water balance was found if groundwater‐unsaturated zone interaction is considered. But the differences between the two groundwater coupling approaches are minor. For the fully coupled model system, streamflow results strongly depend on the simulation quality for precipitation. Two‐way interaction results in net upward water fluxes in up to 25% of the basin area after the rainy season. In total, two‐way interaction increases basin averaged recharge amounts. The evaluation with CPC and GLEAM indicates a better performance of the fully coupled simulation. The impact of groundwater coupling on LSM and atmospheric variables differs. Largest differences occur for the variable recharge (26%), whereas for atmospheric variables, the basin‐averaged impact is minor (<1%). But locally, a spatial redistribution up to ±5% occurs for precipitation. Key Points: Development of a fully coupled hydro‐meteorological modeling system extending WRF with HMS Implementation of two‐way groundwater‐unsaturated zone interaction in the Noah‐LSM of WRF Model system application and investigation of the impact of coupling for Poyang Lake basin, China